Radiologically inserted gastrostomy: differences of maintenance of balloon- vs. loop-retained devices. (1st December 2016) - Busch, J.D.; Herrmann, J.; Adam, G.; Habermann, C.R.
Abstract: Purpose: To compare outcome and associated complications of ballon- vs. loop-retained devices for radiologically inserted gastrostomy (RIG). Methods: From 2007 to 2011 233 patients (age 63.7 ± 10.6 years) were referred for a RIG because of pharyngeal stricture Intervention was performed with four different devices: balloon-retained – Freka ® GastroTube, Fresenius Kabi ( n = 121); MIC ® Gastrostomy Feeding Tube, Kimberly–Clark ( n = 34); Russell ® Gastrostomy Tray, Cook Medical Inc. ( n = 17); and loop-retained – Tilma ® Gastrostomy Set, Cook Medical Inc. ( n = 50). Follow-up was performed with regard to RIG -related complications, cause of removal and fatalities. Revision-free survival times after RIG were evaluated using Kaplan–Meier analysis and group differences by log-rank tests. For analysis of demographic and methodical variables multivariate Cox regression models were used. Results: With a primary technical success rate of 95.3% (222/233) a total of 92 instances of revisions were necessary in 66 patients (66/233, 28.3%) during follow-up (mean 182.8 ± 86.6 days). The most common complication was tube dislodgement (14.3%). There were no significant differences between the distinct devices ( p = 0.098), but analyzing the data in subgroups of balloon-compared to loop-retained gastrostomy tubes we observed a significantly higher probability of minor complications for the latter ( p = 0.023). Conclusion: As it is significantly less prone to minor complications we recommend the use of balloon-retained gastrostomy tubes to improve the practicability and maintenance of RIG.